Pengaruh Pertumbuhan Ekonomi, Indeks Pembangunan Manusia (IPM), dan Kemiskinan terhadap Tingkat Pengangguran Terbuka di Provinsi Jambi Selama Tahun 2017-2021 - Dessy Anggraini; Neneng Sudharyati; Randa Aslam Putra; Nurman Ramdhan; M. Ilham Nur Putra; Habib Hidayat Putra (Ekonomis: Journal of Economics and Business, 2023)
This study aims to see how much influence economic growth, human development index, and poverty have on the open unemployment rate in Jambi Province. The type of data used in this research is in the form of secondary data obtained from the Central Bureau of Statistics using cross-sectional data from 11 regencies/cities in Jambi Province and time series data for the 2017-2021 period. The data analysis used is panel data analysis with the fixed effect model (FEM). The results showed that economic growth had a negative and significant effect on the open unemployment rate in Jambi Province, the human development index (IPM) had a positive and insignificant effect on the open unemployment rate in Jambi Province while poverty had a positive and significant effect on the open unemployment rate in Jambi Province.